Comparative analysis of mutant plants impaired in the main regulatory mechanisms of photosynthetic light reactions - From biophysical measurements to molecular mechanisms - Tikkanen M; Rantala S; Grieco M; Aro EM (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2022)
Chlorophyll (chl) fluorescence emission by photosystem II (PSII) and light absorption by P700 reaction center chl a of photosystem I (PSI) provide easy means to probe the function of the photosynthetic machinery. The exact relationship between the measured optical variables and the molecular processes have, however, remained elusive. Today, the availability of mutants with distinct molecular characterization of photosynthesis regulatory processes should make it possible to gain further insights into this relationship, yet a systematic comparative analysis of such regulatory mutants has been missing. Here we have systematically compared the behavior of Dual-PAM fluorescence and P700 variables from well characterized photosynthesis regulation mutants. The analysis revealed a very convincing relationship between the given molecular deficiency in the photosynthetic apparatus and the original fluorescence and P700 signals obtained by using varying intensities of actinic light and by applying a saturating pulse. Importantly, the specific information on the underlying molecular mechanism, present in these authentic signals of a given photosynthesis mutant, was largely nullified when using the commonly accepted parameters that are based on further treatment of the original signals. Understanding the unique relationship between the investigated molecular process of photosynthesis and the measured variable is an absolute prerequisite for comprehensive interpretation of fluorescence and P700 measurements. The data presented here elucidates the relationships between the main regulatory mechanisms controlling the photosynthetic light reactions and the variables obtained by fluorescence and P700 measurements. It is discussed how the full potential of optical photosynthesis measurements can be utilized in investigation of a given molecular mechanism. (C) 2017 The Authors. Published by Elsevier Masson SAS.